A Note on the Production of Katha and Cutch in India - Jain, P. P. (Indian Forester, 1980)
Methods for the production of katha and cutch from Acacia calechu (khair) wood, have been described. Information on the suitability of the raw-material ie. Khair wood quality of katha, figures of production and requirements of katha in the country, have been given. Suggestions have also been given to meet the increasing requirements of khair wood and the aspects on which work be taken up.